(E)-3-Bromo-N′-(2,4-dichlorobenzylidene)benzohydrazide - Cao, Guo-Biao (International Union of Crystallography, 2009)
The title compound, C(14)H(9)BrCl(2)N(2)O, was synthesized by the reaction of 2,4-dichlorobenzaldehyde with an equimolar quantity of 3-bromobenzohydrazide in methanol. The molecule displays an E configuration about the C=N bond. The dihedral angle between the two benzene rings is 5.3 (2)°. In the crystal structure, molecules are linked through intermolecular N—H⋯O and C—H⋯O hydrogen bonds, forming chains running along the c axis.